Efikasi Makanan Pendamping Bubur Kanji rumbi Instan dalam Meningkatkan Kadar Hemoglobin dan Menurunkan Status Anemia pada Balita Berat Badan Kurang: The Efficacy of Complementary Foods Instant Kanji rumbi Porridge on Increasing Hemoglobin Levels and Reducing Anemia Status in Underweight Toddlers - Bustami, Bustami; Suryana, Suryana; Junita, Dini; Yunianto, Andi Eka; Kushargina, Rosyanne (Amerta Nutrition, 2025)
Background: Cases of underweight and anemia in Acehnese toddlers are high, requiring urgent intervention. A viable alternative is local food-based supplemental feeding, using high-protein and iron-rich meals. One of the examples is the innovative instant kanji rumbi porridge, which is made from Aceh's local protein sources. Objectives: The study aimed to analyze the effect of instant kanji rumbi porridge on hemoglobin (Hb) levels and the anemia status of underweight toddlers through a cluster-randomized control trial design. Methods: The study was conducted in three community health centers in Aceh Besar district and 15 posyandu (integrated service posts) clusters. 46 subjects selected based on the inclusion and exclusion criteria (23 in the intervention group and 23 in the control group). The intervention of instant kanji rumbi porridge was administered for 3 months, with each participant consuming it twice daily. Results: The instant kanji rumbi porridge intervention was successful in reducing the anemia rate from 92.3% of anemic toddlers at baseline to 60.7% by the end of the study. The consumption of instant kanji rumbi porridge significantly increased the energy and nutrient intake of the toddlers both before and after the intervention, as well as within the intervention groups. All groups exhibited an increase in Hb levels; however, the rise in the intervention group was substantially greater than that in the control group (p-value=0.013). Conclusions: Instant kanji rumbi porridge has the potential to be used as a complementary food for toddlers to increase macro and micronutrient intake, especially iron, hence elevating hemoglobin levels and reducing anemia in this age group.